(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Introduction: Increased human health concerns related to the natural environment and climate change are having a growing impact on nursing practice. This past year in Canada, for example, British Columbia reported the highest number of heat related deaths, followed by devastating forest fires in many provinces that have disproportionately impacted Indigenous Peoples. Nurses are well positioned to address the direct health impacts associated with climate change. As a result, nurses require an increased level of ecoliteracy to address the health impacts linked to climate change. The role of the nurse in addressing the health impacts of climate change are vast, ranging from direct patient care, education and advocacy, their role includes supporting individuals, communities, and populations to mitigate, adapt and build resiliency in the face of a changing climate. Background: Regulatory and professional associations support the professional emphasis on the significance of ecoliteracy yet there is insufficient understanding of the resistance to the content in nursing curricula. Although current literature supports an increased emphasis on the integration of ecosystem health concerns and the impact on human health within undergraduate nursing education, there is a paucity of empirical evidence regarding nursing educators’ perspectives on the subject. This study is a first step in gaining a greater understanding of the perspectives of nurse educators on ecoliteracy within undergraduate nursing education programs in one Canadian province. Methods: This qualitative research study included 13 nurse educators from three diverse academic settings. Data were collected using semi-structured, open-ended interview questions, followed by content analysis of the data. Results: Data analysis revealed five key themes: a) importance of ecoliteracy in undergraduate nursing programs; b) current integration of ecoliteracy concepts in curricula; c) future considerations for ecoliteracy content; d) barriers to the inclusion of content supportive of ecoliteracy in curricula; e) strategies to address barriers. While educators feel that ecoliteracy is important in undergraduate nursing, they noted that the current integration of climate content in the curriculum is uneven. Barriers and potential strategies to integrating this content are identified. Conclusion: The findings of this study can be used for curriculum revision and to stimulate innovation and research in nursing education. This study creates the opportunity for a larger scale replication study, pilot studies of the integration of concepts that would support ecoliteracy, and further research on the topic. This study identified that many complexities are involved in achieving ecoliteracy in nursing education and suggest that while threading of content can address the urgent need, further research is required to identify entry to practice requirements for undergraduate nursing programs.